The Influence of Trust Using E-Commerce on Online Purchase Decisions in The Class of 2019 Student of Business Administration at Makassar State University - M Riswandi; Muh Rizal S; Aris Baharuddin; Risma Niswaty; Andi Aslinda (Pinisi Business Administration Review, 2022)
This study aims to find out how the influence of trust using e-commerce on online purchasing decisions on business administration students at the Makassar State University class of 2019. This study uses quantitative research methods. Data collection techniques used are through observation, questionnaires, interviews and documentation. The sample used in this study was the entire population, which was 80 students in the 2019 batch. The data obtained from the research results were processed using data analysis and using the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and inferential statistical analysis. . The results showed that the indicators used in each of these variables indicate where consumer confidence is in the good category. For indicators on the purchasing decision variables are in the good category. Based on the correlation test, there is a strong/high relationship between the two variables. So it can be concluded that there is a significant influence between consumer confidence in using e-commerce on online purchasing decisions in Business Administration students, Faculty of Social Sciences, Makassar State University.